Rancang Bangun Sistem Informasi Desa Menggunakan Framework Codeigniter 4 Bagian Kelahiran dan Kematian pada Desa Cageur - Safira Putri Nabila; Hidra Amnur (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
Country Information System is the sytem that build in to help the country government do the governemnt administration especially population of people department especially for every birth and dead of peolple and its administration. Where with in-put of nominal of birth and dead with on-line system, we can get information of total population of peolple due to birth and dead automatically and type of birth and dead administaration letter.